(a+3b)+(3a-b)i=6+6i

Simple and best practice solution for (a+3b)+(3a-b)i=6+6i equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+3b)+(3a-b)i=6+6i equation:


Simplifying
(a + 3b) + (3a + -1b) * i = 6 + 6i

Remove parenthesis around (a + 3b)
a + 3b + (3a + -1b) * i = 6 + 6i

Reorder the terms for easier multiplication:
a + 3b + i(3a + -1b) = 6 + 6i
a + 3b + (3a * i + -1b * i) = 6 + 6i
a + 3b + (3ai + -1bi) = 6 + 6i

Reorder the terms:
a + 3ai + 3b + -1bi = 6 + 6i

Solving
a + 3ai + 3b + -1bi = 6 + 6i

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3b' to each side of the equation.
a + 3ai + 3b + -3b + -1bi = 6 + -3b + 6i

Combine like terms: 3b + -3b = 0
a + 3ai + 0 + -1bi = 6 + -3b + 6i
a + 3ai + -1bi = 6 + -3b + 6i

Add 'bi' to each side of the equation.
a + 3ai + -1bi + bi = 6 + -3b + bi + 6i

Combine like terms: -1bi + bi = 0
a + 3ai + 0 = 6 + -3b + bi + 6i
a + 3ai = 6 + -3b + bi + 6i

Reorder the terms:
-6 + a + 3ai + 3b + -1bi + -6i = 6 + -3b + bi + 6i + -6 + 3b + -1bi + -6i

Reorder the terms:
-6 + a + 3ai + 3b + -1bi + -6i = 6 + -6 + -3b + 3b + bi + -1bi + 6i + -6i

Combine like terms: 6 + -6 = 0
-6 + a + 3ai + 3b + -1bi + -6i = 0 + -3b + 3b + bi + -1bi + 6i + -6i
-6 + a + 3ai + 3b + -1bi + -6i = -3b + 3b + bi + -1bi + 6i + -6i

Combine like terms: -3b + 3b = 0
-6 + a + 3ai + 3b + -1bi + -6i = 0 + bi + -1bi + 6i + -6i
-6 + a + 3ai + 3b + -1bi + -6i = bi + -1bi + 6i + -6i

Combine like terms: bi + -1bi = 0
-6 + a + 3ai + 3b + -1bi + -6i = 0 + 6i + -6i
-6 + a + 3ai + 3b + -1bi + -6i = 6i + -6i

Combine like terms: 6i + -6i = 0
-6 + a + 3ai + 3b + -1bi + -6i = 0

The solution to this equation could not be determined.

See similar equations:

| x×x-3/x= | | x×x-3/x=18 | | 4x^2=57 | | 10v-3=8v+9 | | 3y-3(-33)=2y+2(-33) | | 4b+4b+4b= | | 2=9z-3z+2-6z+4+z | | 3m+6m-10m=3+7-4+m | | .4(7-3x)=9+(4x-1) | | 5x+8x+11x= | | -40x+36x=30x-45 | | 2b^2+36-9=0 | | 4x-3=9x+9 | | 5x^3-3x^2-5x+3=5x^2-4x-1 | | y=[100+.75(y-150)]+100+100 | | 2v^2-3v+1=0 | | (x^2)+(11x)=0 | | y=-16+4x | | y=4x+-16 | | 2x+20=60+x | | 4(3x+7)=16 | | x^2-4x^2+3=0 | | (x^2)-(6x)=0 | | (4x^2+2x)(5x-4)= | | -1.5x+y=5 | | (x^2)-(6x)=o | | (5x-3)(x+1)(x-1)=0 | | 3x-6=5x+60 | | 5y+7=2y+11 | | -13+2x=-52+35x(fraction) | | 10a+b=8a+8b | | 43x+7=16 |

Equations solver categories